Uzbekistan's Transition To A Green Economy: Current Challenges And Prospects For Sustainable Development - Xudoyorov Azizbek Avaz o‘g’li (Academia One Publishing, 2025)
Today, countries around the world are facing environmental challenges such as climate change, depletion of natural resources, and loss of biodiversity. As an alternative solution to these problems, there is an increasing need to transition to a "green economy" that reduces negative environmental impacts and creates the basis for equitable development. This article analyzes the need for transition to a green economy in Uzbekistan, existing problems, their causes, and economic and environmental factors. The main goal of the study is to identify the main principles and strategic directions of transition to a green economy in the conditions of Uzbekistan, assess existing problems, and develop scientifically based recommendations for their elimination
Keywords: green economy; sustainable development; environment